Primary Necrobiotic Xanthogranulomatous Sialadenitis with Submandibular Gland Localization without Skin Involvement - Myunghee Kang; Na Rae Kim; Dong Hae Chung; Jae Yeon Seok; Dong Young Kim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2019)
Necrobiotic xanthogranulomatous reaction is a multiorgan, non-Langerhans cell histiocytosis with an unknown etiology. Occurrence in the salivary gland is extremely rare. We recently identified a case of necrobiotic xanthogranulomatous sialadenitis in a 73-year-old Korean woman who presented with a painless palpable lesion in the chin. There was no accompanying cutaneous lesion. Partial resection and subsequent wide excision with neck dissection were performed. Pathological examination showed a severe inflammatory lesion that included foamy macrophages centrally admixed with neutrophils, eosinophils, lymphocytes, plasma cells, and scattered giant cells, as well as necrobiosis. During the 12-month postoperative period, no grossly remarkable change in size was noted. Necrobiotic xanthogranulomatous inflammation may be preceded by or combined with hematologic malignancy. Although rare, clinicians and radiologists should be aware that an adhesive necrobiotic xanthogranuloma in the salivary gland may present with a mass-like lesion. Further evaluation for hematologic disease and close follow-up are needed when a pathologic diagnosis is made.